Juristic Concept of the Validity of Statutory Law - Grabowski, Andrzej. author. aut Link
XVI, 595 p.
Keywords: This book presents the theory of the validity of legal norms, aimed at the practice of law, in particular the jurisdiction of the constitutional courts. The postpositivist concept of the validity of statutory law, grounded on a critical analysis of the basic theories of legal validity elaborated up to now, is introduced. In the first part of the book a contemporary German nonpositivist conception of law developed by Ralf Dreier and Robert Alexy is analysed in order to answer the question whether the juristic concept of legal validity should include moral standards or criteria. In the second part, a postpositivist concept of legal validity and an innovative model of validity discourse, based on the juristic presumption of the validity of legal norms, are proposed. The book is a work on analytical legal theory, written from a postpositivist, detached point of view.